Design and implementation of controller for energy efficient operation in building - He, Tingting (2015)
With the concern of global warming and the change of climate, numerable implementation is launched up to reduce the environmental impact. Energy Efficient is the one approach to contribute to the environment protection, a way of managing and restraining the growth in energy consumption. Moreover, it is researched that buildings consume approximately 32% of total final energy consumption with overall energy consumption. With the constraint natural resources of Singapore, increasing population and demand of electricity energy, electricity energy is one of the key to affect the Singapore’s live and economy in resent time and in the future. Overall the years, the saving of energy with a building are significant and benchmarked. This study is aimed to exploit the possible energy reduction to the residential buildings during its peak hours, research on daily load profiles of 1 or 2 rooms, 3 rooms, 4 rooms and 5 rooms’ public housing. Fuzzy logic is implemented to build up the profile and control the peak shaving. A ranking is decided to the home appliance and control the on/off of the appliances, as result of load reduction to the load during the peak hours.